Non-linear pricing in oligopoly - Erwin Amann (Verein für Socialpolitik, 2010)
Price discrimination is an extensively studied subject in monopoly behavior. Increasing profits, covering fixed cost and reducing distortions are reasons to sell a homogenous good at different prices. Price discrimination is however present also in oligopolistic markets. This paper is going to analyze similarities and differences with respect to the literature on monopoly pricing on second degree price discrimination. It is shown that also oligopolies allow even for second degree price discrimination an in this case tend to increase supply even beyond the socially efficient quantity. Facing heterogenous customers competition leads to substantial differences with respect to the determination of the optimal sales plan.
Keywords: D21; D43; D82; 330; Non-linear pricing; oligopoly